1993
DOI: 10.1093/nar/21.12.2955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofSchizosaccharomyces pombeexpression systems

Abstract: (2). The other regulated system was constructed from the tetracycline-inducible system described by Faryar and Gatz (3). The two constitutive promoters were the previously described vectors pART1 (containing the adh promoter; .(4) and pSMl (containing the SV40 promoter; 5).The expression vector REP3, containing the thiamine-inducible nmtl promoter (1), and its derivatives REP41 and REP81 (2), which have lower levels of activity due to mutation, all contain an ATG within their polylinker. This was destroyed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
401
2
13

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(426 citation statements)
references
References 7 publications
10
401
2
13
Order By: Relevance
“…Checking by PCR identified a G418-resistant transformant (strain JW46) that had sustained the desired integration event and segregated 2:2 for G418 resistance when crossed to strain 975. In addition, ain1 ϩ was placed under the control of three versions of the thiamine-regulated nmt1 promoter (the wild-type 3nmt1, the attenuated 41nmt1, and the still weaker 81nmt1) (Basi et al, 1993;Forsburg, 1993), with or without an associated NH 2 -terminal GFP tag (Bähler et al, 1998b). The ain1-specific sequences (70 bp) of the forward primer corresponded to nucleotides Ϫ163 to Ϫ94, and those (76 or 70 bp) of the reverse primers corresponded to the complement of the NH 2 -terminal codons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Checking by PCR identified a G418-resistant transformant (strain JW46) that had sustained the desired integration event and segregated 2:2 for G418 resistance when crossed to strain 975. In addition, ain1 ϩ was placed under the control of three versions of the thiamine-regulated nmt1 promoter (the wild-type 3nmt1, the attenuated 41nmt1, and the still weaker 81nmt1) (Basi et al, 1993;Forsburg, 1993), with or without an associated NH 2 -terminal GFP tag (Bähler et al, 1998b). The ain1-specific sequences (70 bp) of the forward primer corresponded to nucleotides Ϫ163 to Ϫ94, and those (76 or 70 bp) of the reverse primers corresponded to the complement of the NH 2 -terminal codons.…”
mentioning
confidence: 99%
“…To confirm the presence of these introns, the absence of other introns within the fim1 coding region, and the identification of the putative start and stop codons, cDNA sequences were amplified by PCR using the Expand High Fidelity System (Boehringer Mannheim, Indianapolis, IN), one or the other of two cDNA libraries as template, and primers corresponding to fim1 genomic sequences or vector sequences. One library (kindly provided by Dr. C. Albright, Vanderbilt University, Nashville, TN) was constructed in vector pREP3X (Basi et al, 1993;Forsburg, 1993), and the other (Becker et al, 1991) was constructed in vector pDB20. The PCR products were cloned into the pGEM-T Easy vector and sequenced.…”
mentioning
confidence: 99%
“…In the S. cerevisiae complementation test, the Spt4 proteins are expressed from singlecopy CEN plasmids, but no such single-copy plasmid system is available for fission yeast. Instead, we used high-copy vectors that are standard in the field (Forsburg 1993). Therefore, mutations that cause functional deficits at low gene dosage in budding yeast might be missed at high gene dosage in fission yeast, e.g., because increased production of the mutant Spt4 results by mass action in sufficient Spt5-Spt4 complex to support cell growth at 37°C.…”
Section: Deletion Of Spt4 In S Pombementioning
confidence: 99%
“…Therefore, mutations that cause functional deficits at low gene dosage in budding yeast might be missed at high gene dosage in fission yeast, e.g., because increased production of the mutant Spt4 results by mass action in sufficient Spt5-Spt4 complex to support cell growth at 37°C. We attempted to down-regulate transcription of the plasmid-borne nmt1-spt4 + cassette by inclusion of thiamine in the growth medium (Forsburg 1993) and found that the plasmid still complemented growth of the spt4D strain at 37°C (data not shown), implying that Spt4 is indeed produced in functional excess from the high copy plasmid.…”
Section: Deletion Of Spt4 In S Pombementioning
confidence: 99%
See 1 more Smart Citation